Editorial. Da transversalidade temática e concetual da investigação em educação. - Manuela Terrasêca (Universidad de Granada, 2012)
This issue of JETT - Journal for Educators, Teachers and Trainers can be considered an important statement as a scientific journal characterized by internationalization, innovation and transversality. Assembling a significant number of articles, it is easy for us to understand that they are the result of a growing cooperative work between researchers, and touching updated and innovative problems. These contributions can be grouped in three parts, the first focusing on the issues of communication and new technologies of information and communication. The importance of this group of articles is precisely the presentation of educational experiences that may contribute to build an alternative to breakdown and isolation. In a second block, under the title "From early childhood education to higher education - reflecting on different practices," we find a set of articles that somehow express how educational issues and specific themes are thought of in very specific contexts and purposes. Finally, two articles confront us with a reflection about the past and future of Education Sciences and the research that is carried out in this field. The birth of Educational Sciences, in Argentina, a century ago, and reforms developed in a consistent and cohesive way, since three decades ago, in Finland, which established the educational system of this country in a remarkable example, constitutes two important contributions, among the twelve remaining, to consider this issue of JETT as a high quality document.